2017
DOI: 10.1016/j.fuel.2017.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Steam exploded pine wood burning properties with particle size dependence

Abstract: Power generation using waste material from the processing of agricultural crops can be a viable biomass energy source. However, there is scant data on their burning properties and this work presents measurements of the minimum explosion concentration (MEC), flame speed, deflagration index (K st ), and peak pressure for pulverised pine wood and steam exploded pine wood (SEPW). The ISO 1 m 3 dust explosion vessel was used, modified to operate on relatively coarse particles, using a hemispherical dust disperser o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…FPM 2.5 and CPM emissions are influenced by the type of fuel, combustion process, operating conditions, and flue gas exhaust temperature. , In this study, FPM 2.5 concentrations were lower than CPM concentrations in all emission groups with the exception of WOD. In WOD, high FPM 2.5 concentrations could be the result of incomplete combustion of fuel, low flue gas temperature, and more ash content in the wood . Yang et al reported that the ash content, flue gas temperature, and APCDs system can affect FPM 2.5 concentrations in a wood-fired boiler.…”
Section: Results and Discussionmentioning
confidence: 99%
“…FPM 2.5 and CPM emissions are influenced by the type of fuel, combustion process, operating conditions, and flue gas exhaust temperature. , In this study, FPM 2.5 concentrations were lower than CPM concentrations in all emission groups with the exception of WOD. In WOD, high FPM 2.5 concentrations could be the result of incomplete combustion of fuel, low flue gas temperature, and more ash content in the wood . Yang et al reported that the ash content, flue gas temperature, and APCDs system can affect FPM 2.5 concentrations in a wood-fired boiler.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Further research is needed, in order to establish a novel, qualitative, rapid testing analytical techniques, such as FTIR ATR or NIR, as QC techniques for Biocoal, most of the work being the identification of particular wavenumbers/bandwidths relevant for the properties of the solid fuel. It would be even better if correlations between such characteristic wavenumbers/bandwidths and performance of the solid fuels in [193] ☑ Time-consuming Ultimate analysis � Dedicated (CHNS*) analysers ☑ Allow calculation of the stoichiometric amount of oxygen/air [181,182] ☑ Allow estimation of the change of NO x emissions ("fuel NO x ") and SO x depending on the used fuel ** [183][184][185][186][187][188][189][190] Fire and explosion characteristics � 20 L or 1 m 3 spherical vessel � Hartmann apparatus � Layer Ignition Temperature Apparatus � Self-Ignition (in volume) Temperature apparatus � Goldberg-Greenwald apparatus ☑ Parameters necessary for ATEX assessment and risk prevention (fire and explosion safety) [194] ☑ Assessment of reactivity [33,85,[195][196][197] ☑ Knowledge about ignition and flame propagation [34,[197][198][199] ☑ Time-consuming * -not all analysers allow determination of S content. ** -requires information on fuel N/S conversion to NO x /SO x .…”
Section: Discussionmentioning
confidence: 99%
“…This makes the fuel less sensitive to biodegradation, self-heating and moisture uptake [25][26][27][28][29][30][31][32]. Reactivity of torrefied biomass is typically increased, in comparison to the original feedstock, which is important in terms of subsequent use of torrefied material as a fuel in combustion and gasification processes [33,34].…”
Section: Production Of Biocoal Using Dry and Wet Torrefactionmentioning
confidence: 99%
“…The different sizes and various shapes of organic powder make the interpretation of organic dust explosion difficult and complicated [14,15]. Saeed et al [16,17] suggest that fine biomass facilitates increased mass-burning with high flame speed. Therefore, the potential risk derived from the organic dust including explosion and ignition imparts huge hidden danger to the dust-processing workshops [5,6,7].…”
Section: Introductionmentioning
confidence: 99%